Moderate cold exposure in the Faroe fishing industry. - Lundqvist, Gunnar R; Jensen, Preben L; Solberg, H E; Davidsen, E (Scandinavian Journal of Work, Environment & Health, 1990)
Differences in female workers' finger temperatures, manual dexterity, ratings on thermal comfort, and local cooling exposure were studied in three factories in the Faroe Island fishing industry. Environmental temperatures in the factories varied from 5 to 19 degrees C with vertical gradients of 7 degrees C/m, and the mean temperatures of the flushing water varied from 2 to 15 degrees C. Finger temperature varied from 12 to 24 degrees C when measured 2 min after work was stopped, and about one-third of the women experienced thermal discomfort in the fingers during work. The fish temperature increased, on the average, less than 1 degrees C during passage through the production room, notwithstanding the thermal differences among the factories. These findings should be used in attempts to reduce the cold exposure of the workers; but also improved control should be recommended for both environmental and water temperatures in the factories.